Analisis Penerapan Metode Pencatatan Terhadap Persediaan Barang Dagang Benang Pada PT. Mitra Bangun Cemerlang (MBC) Tahun 2022 - andy Januar Permana; Rasyiddin, Ahmad; Eliana rosaliana; Hurian Kamela (JURNAL EKONOMI, BISNIS DAN HUMANIORA, 2022)
Inventories are part of current assets and also one of the means to carry out company activities needed by various types of companies such as trading, manufacturing and service companies. Recording is a way of working or a process system for recording or writing (in and out) of a transaction activity in a complete notebook. Meanwhile, the recording method has the goal of facilitating the implementation of an activity in determining or achieving a certain goal. PT. Mitra Bangun Cemerlang (MBC) is engaged in the textile sector. This research focuses on recording the inventory of yarn merchandise. The researcher wants to examine how "The Application of the Method of Recording Yarn Merchandise Inventory at PT. Mitra Bangun Cemerlang (MBC) in 2022”. The method of recording yarn merchandise inventory applied at PT. Mitra Bangun Cemerlang (MBC) is still manual and does not use the system yet. The manual recording method for yarn merchandise inventory uses the perpetual method. Every process or transaction of incoming and outgoing thread merchandise is always recorded. The method of recording yarn merchandise inventory at PT. Mitra Bangun Cemerlang (MBC) has several processes, namely the production of yarn from the production machine whenever there is income, it is always recorded, checking the quality of the yarn, grouping each grade of yarn, re-weighing the yarn produced in the packing section, packing the yarn using product cardboard, labeling on product cardboard for yarn identity, handover of yarn to the packing warehouse, making daily yarn stock reports in the packing warehouse, daily yarn stock reports given to the warehouse admin for cross-checking, reporting back to superiors by sending reports via email. Of course, some of these processes will more or less encounter errors due to inaccuracies in recording. But apart from that, all methods of recording yarn trade goods at PT. Mitra Bangun Cemerlang (MBC) in 2022 is still being used, proven to be safe and well monitored, although some need to be upgraded and the accuracy needs to be improved.